The Development of Digital Library User Interface by Using Responsive Web Design and User Experience - Dimas Sasongko; Ridi Ferdiana; Rudy Hartanto (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The digital library has the purpose of providing services to the user, therefore, user experience factor and adjusting the display device diversity becomes the main thing to consider in building a digital library. The digital library is visited by many users because it provides a lot of information so that the existing content should be accessible anywhere, anytime and using a variety of devices. This research focuses on the design of digital library interface that adapts to the user experience and a variety of devices. The method used in this study is testing the user experience for the evaluation of digital library interface and Responsive Web Design for the development of digital library interface. The confidence interval is used as the analysis of the test data. Implementation of the user experience and Responsive Web Design in the digital library interface design proposals can improve the estimated percentage of success and task time users.